Mechanoactivation and colour properties of malayaites doped with lanthanoids - Zvonková Marcela; Luxová, Jana; Trojan, Jakub; Trojan, Miroslav (University of Pardubice, 2015)
The study deals with the preparation of the inorganic pigments of general formula CaSn0.855Cr0.045Ln0.1SiO5±δ, belonging to the group of the malayaites, where Ln = La, Ce, Pr, Nd, Sm, Eu and Gd (LMREE). The malayaite samples were prepared in powdered form by the solid state reaction. As initial components were used the following basic raw materials: calcium carbonate, tin oxide, chromium oxide, silicon oxide, and oxide of the respective lanthanoid serving as the dopant. The reaction mixtures were homogenised and ground in the planetary mill for five hours. After mechanoactivation, they were calcinated at the temperatures from 1200 °C to 1450 °C in the electric furnace for four h. All the prepared pigments were applied / converted into a ceramic glaze P07410 and very interesting colours obtained: brown pink, deep burgundy, and red carmina shades.. The colour characteristics were described by CIE L*a*b* system (1976). From the particle size distribution, it is evident that all three parameteres, d(0.1) μm, d(0.5) μm, and d(0.9) μm have increased with temperature. Finally, as confirmed experimentally, the mechanoactivation has led to very thin granules, increasing the brightness (L*).